An integrated approach of Fuzzy AHP and Fuzzy TOPSIS in modeling supply chain coordination - Shukla, Rajendra Kumar; Garg, Dixit; Agarwal, Ashish (Production & manufacturing research, 2014)
In improving overall supply chain performance, coordination of supply chain of trading partner plays a crucial role. For allocating the components or services to trading partner, it would be significant to analyze level of coordination in their supply chain. This paper presents how Analytic Hierarchy Process and Technique for Order Preference by Similarity to Ideal Solution in Fuzzy environment can be integrated for a more consistent evaluation and prioritization of trading partner based on four coordination criteria namely joint decision-making, information sharing, use of information technology tools, and resource sharing determined by factor analysis of survey data and expert opinion. A case study of Indian automotive parts manufacturing company is described to illustrate the application of the proposed method. Fuzzy AHP is used to calculate relative weights of each coordination criterion and then partners are ranked based on closeness coefficient, calculated for each partner using Fuzzy TOPSIS.